CHILD RIGHTS TO THE SPORT: RELATIONSHIPS WITH THE PRINCIPALS OF EDUCATIONAL SPORT (Fiep Bulletin - online, 2015)
In the current society, the new sport concept, seeks to guarantee and to motivate all the people to the sporting practice. The Sport-educational has as function the man's formation, because, it should be practiced by all and given as opportunity to each child. In this kind of sport the most important is the participation, seeking a better development in their behavior besides the political and social aspects. It is believed, that these objectives can be obtained through the awareness of the professionals that  act in the Sport-educational.  The same should be understood through the Rights and Principles of the Sport-educational that are related to the context of the Science of Human Motricity, because they link to the man's movement and its significance for the child's formation in the school ambit. The proposal of this study was to verify the relationships of the Rights with the Principles of the Sport-educational, tends as reference the Letter of the Child's Rights in the Sport (Panatlhon/Avignone, 1995), it has the purpose of building a comparative map starting from eight (08) International and National documents; the selection and definition of sixteen (16) Rights; the classification of six (06) more representative Rights, relating them to five (05) principles of the Sport-educational. It is concluded that the extracted conclusions of the study agree with the epistemology of Tubino (2002), in  which the right to the sporting practice is one of the methodologies used in the man's formation in the sense of civilizating process, contributing to the construction of a homogeneous society, preserving and valuing the human relationship. Destarte, in obedience to the Principle of Juridical Isonomia, the Constitution of the Brazilian Federal (CRFB) in its 5th article  - Caput, consecrates that " all are same before the law, without distinction of any nature, being guaranteed to the Brazilians and the  foreigners resident in the country the inviolability of the right to the life, to the freedom, to the equality, to the safety and the property... " and like this the child as " subject of right " he/she has at your disposal the warranty of the access to the sport practice according to the Great Diploma in the article 217.The documents were elaborated with the purpose of offering to the children and the society in general physical activities that assist to your needs with professional quality. These can also be useful to base the public and social politics in the national and international ambit, seeking to develop the habit of physical activities in any social dimension of the sport in universal ambit.
Keywords: SPORT; RIGHT; EDUCATIONAL